Analysis of Physical Tourism Tickets: Can Security Printing be Used? - Amri, Lala Hucadinota Ainul (P3M Politeknik Negeri Media Kreatif, 2023)
Selling physical tickets at tourist destinations is often a problem in the world of tourism. The number of brokers and fake tickets is always the main problem. Physical tickets are very easy to counterfeit and very easy to distribute to irresponsible brokers. As a result, many tourists are deceived and often have to pay twice or even more just because they bought fake tickets. This research analyzes the problems caused by physical tickets and analyzes alternative security printing solutions that can be applied to ticketing systems using descriptive qualitative research methods. The results of this research are that ticketing using security printing will require greater costs and still pose a risk of ticket counterfeiting. Security printing might have benefits if it were given more value, such as embossing for braille letters aimed at blind tourists. However, for greater benefits, digital ticketing will have a smaller risk of counterfeiting and have greater profits.